The State of Food and Agriculture 1998 - Food; Agriculture Organization of the United Nations (United Nations, 1998)
In addition to the usual review of the recent world food and agriculture situation, each issue of The State of Food and Agriculture from 1957 has included one or more special studies of problems of longer-term interest. This year’s edition focuses on rural non-farm income in developing countries.